CHILDREN MORTALITY FROM COMMUNICABLE DISEASES INCHILD TEACHING HOSPITAL - Al-Malikey, Maysaa; Hussan, Ibtesam; Mubark, Istabraq (Iraqi Journal of Science, 2024)
Hospital based data on mortality rate from communicable diseases is a reflectionof what is obtainable in a community at large. Therefore; data obtained from suchreview is usually beneficial in re-evaluating existing services and in improvingfacilities and patients care. The aim of this study was to evaluate the mortalitypattern of children admitted into the Children Teaching Hospital from February2004 to December 2006. There were 3,267 admissions during the study period. Themedical charts of all patients aged one month to 16 years were recorded, neonataland surgical cases were excluded. One hundred and seventy one deaths occurred inthe children giving mortality rate of 5.2%. Fifty two patients (88%) were under 5years. Most of the deaths occurred between January and March. The commonestcauses of death were pneumonia, bacterial meningitis; while 12% of patients wereabove 5 years of age, the visceral leishmaniasis and pneumonia were thepredominant causes. Health intervention programs such as integrated managementof childhood illnesses and primary health care, which have been shown to reducechildhood deaths significantly, need to be intensified in order to achieve the MDG4by 2015.